1962
DOI: 10.1128/jb.84.2.258-268.1962
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOLOGICAL ROLE OFBRUCELLA ABORTUSCELL WALLS

Abstract: AND EDGAR RIBI. Immunological role of Brucella abortus cell walls. J. Bacteriol. 84:258-268. 1962-Cell walls and protoplasm were prepared from organisms disrupted in a refrigerated pressure cell. Cell walls were purified by sedimentation in a linear glycerol gradient. Antigens capable of protecting mice against infection with Brucella abortus and of reacting with antiserum prepared against whole cells were present chiefly in the cell wall; substances lethal to mice and responsible for primary inflammation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1970
1970
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…abortus, were investigated by Foster and Ribi. (30) The effects of the infection, which was intraperitoneally delivered to mice, was assessed 2 weeks postinoculation. Likelihood statistics indicated that the data could best be fit to an optimized exponential model (Table VI).…”
Section: Bootstrapped Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…abortus, were investigated by Foster and Ribi. (30) The effects of the infection, which was intraperitoneally delivered to mice, was assessed 2 weeks postinoculation. Likelihood statistics indicated that the data could best be fit to an optimized exponential model (Table VI).…”
Section: Bootstrapped Resultsmentioning
confidence: 99%
“…Mice were the test subjects for analyzing the effects of intraperitoneally delivered Br. abortus (30) and assessed 2 weeks postinoculation (data listed in Table V). Likelihood statistics indicated that the data could best be fit to an exponential model (Table VI) with the rate parameter k = 0.02475 with an approximate N 50 of 28 CFU.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Although the endotoxic activity of B. abortus strain 19A is about as great as that of strain 2308 (10), strain 19A is less virulent than strain 2308 and is commonly used for vaccination of cattle. That is, in cattle and guinea pigs, strain 19A does not cause as severe an infection as strain 2308, and, if given to heifers 6 to 8 months old, strain 19A is an effective vaccine (4).…”
Section: Vol 2) 1970mentioning
confidence: 97%
“…Cell walls and protoplasm (or cytoplasm) were prepared from each cell suspension by methods described by Foster and Ribi (10), or Foster, Cowan, and Maag (9). ECP was prepared by aqueous ether extraction and ethyl alcohol precipitation (10).…”
mentioning
confidence: 99%